Investigating the solid-state diffusion at the interface of Ni/Ti laminated composite. (March 2022) - Luo, Jie; Yarigarravesh, Mahdireza; Assari, Amir Hossein; Amin, Nima Hajimirza; Tayyebi, Moslem; Paidar, Moslem
Abstract: The fabrication of Ni/Ti laminated composite via cross accumulative roll bonding (CARB) and subsequent annealing treatment has been studied. The relationships between annealing conditions and microstructure at interfaces of Ni/Ti have been investigated by SEM, XRD, and EDS analyses. The results show that the layers were well-bonded by the CARB process, and by increasing the temperature and time of annealing treatment, the interfacial layers grew as a result of the interdiffusion of Ni and Ti atoms. The main intermetallic phases were NiTi and NiTi2, both of which obeyed linear kinetics of growth. However, the calculated activation energy of NiTi was lower than that of NiTi2, indicating the comparable growth of NiTi. Further, based upon the results of tensile tests, the ultimate strength of samples decreased as the intermetallic layers grew; the detachment of layers and the intergranular fraction of intermetallic compounds were the main fracture mechanisms. Highlights: Ni/Ti laminated composite was produced by using the CARB process and post-annealing. The following sequence of phases was detected: Ti/NiTi2 /NiTi/Ni3 Ti/Ni The thickness of NiTi2 and NiTi layers rose as the temperature and time of annealing treatment increased. As the intermetallic layers grew, the values of ultimate tensile strength and elongation decreased and fluctuated, respectively.